The New Common How the COVID-19 Pandemic is Transforming Society - Aarts, Emile; Fleuren, Hein; Sitskoorn, Margriet; Wilthagen, Ton (Springer Nature, 2021)
This open access book presents the scientific views of some fifty experts on how they believe the COVID-19 pandemic is currently affecting society, and how it will continue to do so in the years to come. Using the concept of a "common" (in the sense of common values, common places, common goods, and common sense), they elaborate on the transition from an Old Common to a New Common. In carefully crafted chapters, the authors address expected shifts in major fields like health, education, finance, business, work, and citizenship, applying concepts from law, psychology, economics, sociology, religious studies, and computer science to do so. Many of the authors anticipate an acceleration of the digital transformation in the forthcoming years, but at the same time, they argue that a successful shift to a new common can only be achieved by re-evaluating life on our planet, strengthening resilience at an individual level, and assuming more responsibility at a societal level.